Optimizing rearing duration to improve broiler production indices in conventional open sided and tunnel ventilated closed sheds during summer season - A P S Sethi and Chanchal Singh, Manmeet Kaur, Amit Sharma Ravikant Gupta, Yashpal Singh (Indian Journal of Animal Production and Management, 2019)
Present study was conducted to compare the effect of the rearing duration, housing type and stockingdensity on resource use efficiency of broiler production during summer. A total of 984 day old broiler chickswere subjected to different treatments i.e. T0 (birds with floor space,1.0/ft2/ bird in open sided conventionalbroiler house (OSCBH) as control, while different treatments in tunnel ventilated environment controlbroiler house (ECBH) were T1, T2, T3, T4 and T5 with floor space of 1.0, 0.9, 0.8, 0.7and 0.6 ft2 per bird,respectively. Growth performance and economic returns in all treatments in both types of housing decreasedafter 5th week of age. After 5th week, body weight (1624.19vs1386.01 g),feed intake(1016.53 vs 924.53g), FCR(4.37vs3.94), PER(1.22vs 1.16), EER(14.13vs 12.59) and economic return was significantly(Pâ‰¤0.05) better in ECBH (T2) than OSCBH (T0) even at 10% higher stocking density.